Intrinsic fragment spins generated in the reactions of 20Ne with 197Au and 238U at 12.6 MeV/nucleon - Morrissey, D. J.; Wozniak, G. J.; Sobotka,L. G.; Pacheco, A. J.; McDonald, R. J.; Hsu, C. C.; Moretto, L. G. (North Holland Publishin Co., 1982)
Fil: Morrissey, D. J. National Superconducting Cyclotron Laboratory, Michigan State University; Estados Unidos